Zircon Genesis and Geochronology for the Zhangbaoshan Super-Large Rubidium Deposit in the Eastern Tianshan, NW China: Implication to Magmatic-Hydrothermal Evolution and Mineralization Processes - Zhi, Jun; Lei, Ruxiong; Chen, Boyang; Muhtar, M. N.; Feng, Zhijie; Zhang, Kai; Cai, Yuanfeng; Wu, Changzhi (Frontiers in Earth Science, 2021)
The Zhangbaoshan (ZBS) super-large Rubidium deposit, located in the Eastern Tianshan, is a typical granite-type Rb deposit. The ZBS deposit is mainly hosted in the highly evolved Baishitouquan (BST) pluton , which exhibit five lithological zones from the bottom to the top: leucogranite (zone-a), amazonite-bearing granite (zone-b), amazonite granite (zone-c), topaz-bearing amazonite granite (zone-d) and topaz albite granite (zone-e). Two types of zircon were identified from the BST pluton. Type-I zircons, mainly occur in the zone–a, are characterized by obvious oscillatory zoning, high Zr contents (47.4–67.3 wt% ZrO2) and Zr/Hf ratios (21.72–58.23), low trace element concentrations, and heavy rare earth elements (HREE)–enriched patterns with prominent positive Ce anomalies (Ce/Ce* = 1.21–385) and strong negative Eu anomalies (Eu/Eu* = 0.008–0.551), indicative of early magmatic zircon. Type–II zircons, mainly occur in the upper zones, exhibit porous and dark Cathodoluminescence images, inhomogeneous internal structure, plenty of mineral inclusions, low Zr (38.7–51.0 wt % ZrO2) and Zr/Hf ratios (3.35–11.00), high Hf (34094–85754 ppm), Th (718–4980 ppm), U (3540–32901 ppm), Ta (86.7–398 ppm), Y (1630–28890 ppm) and rare earth elements (REEs) (3910–30165 ppm), as well as slightly HREE–enriched patterns and significant M–type tetrad patterns with t3 values of 1.51–1.69. It is suggested that the type–II zircons are crystallized from deuteric F–rich fluid during the transition from magmatic to hydrothermal stage of the BST pluton. The F–rich fluid exsolution during the magmatic–hydrothermal transition is one of the most important factors controlling Rb enrichment and mineralization. The type–I zircon samples from zone–a yield concordant ages of 250 ± 2.5 Ma and 250.5 ± 1.7 Ma, respectively, indicating that the BST pluton was emplaced in the Early Triassic. The type–II zircons from zone–c to zone–e yield lower intercept U–Pb ages between 238 to 257 Ma, which may represent the age of F–rich fluid–melt interaction during the transition from magmatic to hydrothermal stage. The mineralization of the ZBS Rb deposit occur shortly after emplacement of the BST pluton in the Early Triassic. Combined with available data, it is suggested that Triassic is an important granitic magmatism and rare metal metallogenic period of the Eastern Tianshan.